1986
DOI: 10.1210/jcem-63-2-418
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biological Phenotypes in Late-Onset 21 Hydroxylase Deficiency

Abstract: We analyzed data from 20 patients with late-onset 21-hydroxylase deficiency (LOHD). Three clinical phenotypes could be distinguished among the 18 women. Seven (39%) presented with clinical features suggesting polycystic ovarian disease (PCOD). However, despite androgen levels similar to those of patients with typical PCOD, high serum LH to FSH ratios were not consistently found. Seven other women (39%) presented with isolated hirsutism, suggesting idiopathic hirsutism. The remaining 4 women (22%) had no manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
2
9

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 21 publications
6
59
2
9
Order By: Relevance
“…Emans et al (31) have reported a patient with LOCAH diagnosed by ACTH testing and HLA studies, an elevated LH level, and PCO by laparoscopy. Dewailly et al (17) have found an elevated LH : FSH ratio in 23% of patients with LO 21-OH deficiency. In many patients with PCOS, dexamethasone treatment is associated with a frequency of ovulation, and can reverse symptoms of hyperandrogenism (5,30).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Emans et al (31) have reported a patient with LOCAH diagnosed by ACTH testing and HLA studies, an elevated LH level, and PCO by laparoscopy. Dewailly et al (17) have found an elevated LH : FSH ratio in 23% of patients with LO 21-OH deficiency. In many patients with PCOS, dexamethasone treatment is associated with a frequency of ovulation, and can reverse symptoms of hyperandrogenism (5,30).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, sonographic abnormalities of the ovaries may be similar in women with PCOS and women with adrenal enzyme defects (29,30). Although the classical laboratory findings in PCOS are an elevated level of serum LH and an elevated LH : FSH ratio, this can also be found in LOCAH (17,31,32) and approximately 60% of patients with PCOS do not have this inappropriate gonadotropin secretion (33,34). Emans et al (31) have reported a patient with LOCAH diagnosed by ACTH testing and HLA studies, an elevated LH level, and PCO by laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…those with hyperandrogenic features or ovulatory/menstrual dysfunction). Various investigators have suggested the use of unstimulated levels of 17-OHP as a predictor of NCAH [24,57,87,88]. Levels of 170-300 ng/dL have been found to be useful as a screening tool, best if obtained in the morning and, most importantly (to reduce false positives), in the follicular (preovulatory) phase of the menstrual cycle Among 129 Portuguese women with hyperandrogenism and menstrual dysfunction, 87% of women with NCAH, 25% of lean women with PCOS, 20% of obese women with PCOS, and 7% of control women had basal 17-OHP concentrations >200 ng/dL [20].…”
Section: Diagnosismentioning
confidence: 99%